PENERAPAN MODEL DISCOVERY LEARNING BERBANTUAN MEDIA QUIZIZZ UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DI MTSN 4 KOTA SURABAYA - Putri, Daffania Tsabitah Zuhra; Sutini; Yuliati, Dian (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
The purpose of this study is to analyze the effects of using the discovery learning model with the use of Quizizz media on the academic performance of seventh graders at MTsN 4 in Surabaya City.  The methodology used for this study is known as Classroom Action Research (PTK). The research involved 32 students from Surabaya City's seventh grade E MTsN 4 class. Two cycles were used to conduct the research.  The four phases of a cycle are preparation (preparation), execution (act), oversight (observation), and analysis (analysis). After collecting data using the learning results test technique, we compared the results using a table that categorized the percentage of learning completeness and then evaluated the data based on students' learning outcomes. Learning outcomes significantly improve with each cycle, according to the research. A score of 21.875% in the extremely bad category, 53.125% in cycle I, and 84.375% in cycle II are all indicative of this improvement compared to pre-cycle activity. Students in seventh grade at MTsN 4 in Surabaya City can benefit from using Quizizz media to supplement the discovery learning methodology.